2021
DOI: 10.1108/emjb-12-2020-0134
|View full text |Cite
|
Sign up to set email alerts
|

Non-financial reporting and company financial performance: a systematic literature review and integrated framework

Abstract: PurposeThe purpose of this paper is to examine the different aspects of non-financial reporting that may influence company financial performance. In particular, the authors present an integrated framework of these features that have a direct impact on the financial sustainability of firms for future researchers to further explore and expand the boundaries of the domain.Design/methodology/approachA systematic literature review of peer-reviewed papers, covering the period 2015–2020, was done, and 41 paper were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Aligning with this principle, we chose to apply to our study the SLR methodology, which has recently been applied in studies published in top-tier management journals such as Journal of Management (Castañer and Oliveira, 2020), Academy of Management Annals (Aguinis et al, 2018), International Journal of Management Reviews (Nofal et al, 2018), Journal of World Business (Christofi et al, 2021). Specifically, an SLR is based on a revision of present research on one or more formulated questions that apply a clear method to identify, choose and critically examine research (Crous et al, 2022;Grant and Booth, 2009), and it often offers scholars and experts a framework that integrates extant knowledge (e.g. Christofi et al, 2019a;Dada, 2018;Nofal et al, 2018;Williams et al, 2021).…”
Section: Selecting the Type Of Methodologymentioning
confidence: 99%
“…Aligning with this principle, we chose to apply to our study the SLR methodology, which has recently been applied in studies published in top-tier management journals such as Journal of Management (Castañer and Oliveira, 2020), Academy of Management Annals (Aguinis et al, 2018), International Journal of Management Reviews (Nofal et al, 2018), Journal of World Business (Christofi et al, 2021). Specifically, an SLR is based on a revision of present research on one or more formulated questions that apply a clear method to identify, choose and critically examine research (Crous et al, 2022;Grant and Booth, 2009), and it often offers scholars and experts a framework that integrates extant knowledge (e.g. Christofi et al, 2019a;Dada, 2018;Nofal et al, 2018;Williams et al, 2021).…”
Section: Selecting the Type Of Methodologymentioning
confidence: 99%
“…The borrowed capital ratio (BCR) is used by credit analysts to determine the creditworthiness of a company, considering that a higher value points to higher financial risk. According to Crous et al [32], we expect a positive relationship between leverage and integrated reporting quality, considering that companies under debt pressure will also be incentivized to be more transparent about their sustainability risks. Dragomir et al [41] identified a moderate positive correlation between BCR and NFRQ.…”
Section: The Relationship Between Financial Performance and Nfrqmentioning
confidence: 99%
“…Another important finding is that the quality of overall ESG management is a positive factor of the quality of non-financial reporting [12]. From another perspective, companies in environmentally sensitive industries tend to issue higher-quality external reports [32]. However, the focus on integrated reporting and various other frameworks (such as the GRI Standards) is marginally relevant to the effects of mandatory non-financial reporting under the NFRD in the European Union.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations of French companies revealed that reporting quality mitigates inefficiencies related to information needs and that governance can drive change through established reporting processes (Houcine et al, 2022). In addition, an organisation's non-financial dimensions directly impact financial sustainability, suggesting an integrated framework to EMJB be explored in the future (Crous et al, 2022). In a public management context, among the different types of social reporting capable of involving all actors by placing the citizen at the centre of the decision-making process (Biondi and Bracci, 2018), Integrated Popular Financial Reports (IPFR) or Popular Reports are the main ones that best suit informational needs, change, and accounting by associating the tool with new disruptive technologies (Grossi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%